2014
DOI: 10.1007/s11552-014-9707-x
|View full text |Cite
|
Sign up to set email alerts
|

Internet Self-Diagnosis in Hand Surgery

Abstract: Background Some Internet sites have programs that attempt to help patients find their diagnosis based on symptoms. This study tested the null hypothesis that there are no factors associated with correspondence between online diagnosis and the hand surgeon's diagnosis in an outpatient hand and upper extremity surgeons' office. Methods Eighty-six outpatients were prospectively enrolled and used WebMD® symptom checker to guess their diagnosis. We collected demographic information, hours spent on the Internet per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 13 publications
1
27
0
2
Order By: Relevance
“…In this case, the user must decide which condition describes their current state best. The likelihood of a user to accurately choose the right diagnosis is associated with the sociodemographic profile/variables of a user, such as education and gender [33]. For example, women and those with higher education were more likely to choose the correct diagnosis [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the user must decide which condition describes their current state best. The likelihood of a user to accurately choose the right diagnosis is associated with the sociodemographic profile/variables of a user, such as education and gender [33]. For example, women and those with higher education were more likely to choose the correct diagnosis [33].…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood of a user to accurately choose the right diagnosis is associated with the sociodemographic profile/variables of a user, such as education and gender [33]. For example, women and those with higher education were more likely to choose the correct diagnosis [33]. Therefore, although having a timely diagnosis is important, it may be counterproductive if the user considers the wrong treatment options owing to a misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the correct diagnosis was listed first more often for common diagnoses than for uncommon diagnoses (38% vs 28%). Additional studies focusing on WebMD found that patients using the symptom checker in a hand surgery clinic correctly guessed a diagnosis matching that of the hand surgeon 33% of the time [32] and that with ear, nose, and throat patient cases, the symptom checker was correct 16% of the time, although the correct diagnosis was listed within the differential list 70% of the time [33].…”
Section: Discussionmentioning
confidence: 99%
“…Tanulmányunk alapján is különbség figyelhető meg a nemek közt, a nők gyakrabban használják az internetet egészségügyi tájékozódásra (a nők 76%-a, míg a férfiak 61%-a minimum havonta). Az interneten olvasottak alapján sokan diagnosztizálják, ill. kezelik önmagukat, melyeknek helyessége, ill. sikeressége nagyon változatos [4,5,6]. Tanulmányunkban a válaszadok közel kétharmada diagnosztizálta már önmagát, bevallásuk szerint több mint egyharmaduk sikerrel járt.…”
Section: Megbeszélésunclassified
“…Az internethasználók aránya 1052%-os növekedést mutatott az ezredforduló óta[1]. Tanulmányok igazolják, hogy egészségügyi tájékozódásra is nagyon sokan az interneten keresik a választ, sokan diagnózis felállítás céljából, sokan diétákra keresnek rá, ill. tüneteik kezelésére használják a világhálót[4,5,6]. A romániai lakosságra vonatkozóan hiányosak az adatok, nincsenek összehasonlító tanulmányok, amelyek nem, végzettség, életkor és régió szerint stratifikálva térképeznék fel az internethasználatot mint egészségügyi információforrás.…”
unclassified